Binary-Ternary Plus-Minus Modular Inversion in RNS - Bigou, Karim; Tisserand, Arnaud (IEEE transactions on computers, 2016)
A fast RNS modular inversion for finite fields arithmetic has been published at CHES 2013 conference. It is based on the binary version of the plus-minus Euclidean algorithm. In the context of elliptic curve cryptography (i.e., 160-550 bits finite fields), it significantly speeds-up modular inversions. In this paper, we propose an improved version based on both radix 2 and radix 3. This new algorithm leads to 30 percent speed-up for a maximal area overhead about 4 percent on Virtex 5 FPGAs.